Calvarial Biopsy Using Augmented Reality Technology: A Case Report and Technical Note - Sharma, Nikhil; Shanahan, Regan M.; Bhatia, Shovan; Kann, Michael R.; Tang, Anthony; Adida, Samuel; Kass, Nicolas M.; Cheng, Lucille; Steuer, Fritz; Head, Jeffrey R.; Raver, Michael; Canton, Stephen P.; Mallela, Arka N.; Biehl, Jacob; Hadjipanayis, Constantinos G.; Andrews, Edward G. (Asian Journal of Neurosurgery, 2025)
Calvarial lesions are uncommonly encountered and are often a slow and progressive process. Biopsies of calvarial lesions can be uniquely challenging due to its proximity to critical structures. Augmented reality (AR) offers a potential alternative to computed tomography guidance that reduces radiation exposure and provides hands-free intraoperative guidance through complex and challenging surgical approaches. The patient is an 86-year-old female with significant past medical history of coronary heart disease. The patient underwent imaging which demonstrated a left parietal lytic skull lesion with extracranial extension. Using Surgical AR (Medivis, New York, New York, United States), a trajectory was planned centered on the lesion. Surgical AR was registered using point-to-point registration reliant on four anatomic fiducials. We used a ground truth, which is a bi-faced adhesive tag that measures 2 cm × 1 cm, with a QR code on each side that the Surgical AR system recognizes. This ground truth was placed on the patient's forehead, which linked to the registered holographic overlay. A small incision was made and after removal of a small portion of the overlying skull, multiple pieces of the lytic skull lesion were sampled. A specimen was obtained for frozen sectioning. Intra-operative pathology was consistent with metastatic carcinoma. Total surgical time was 35 minutes from incision to closure. The frameless AR navigation system successfully allowed accurate location, visualization, and biopsy of a calvarial lesion that had minimal surface landmarks. More so, this was completed without obscuring the surgical field or requiring time-consuming setup or registration.
Keywords: augmented reality (AR); calvarial biopsy; hands-free; neuronavigation; guidance